Pembangunan Sistem Interpretasi Hasil Tes MMPI (Minnesota Multiphasic Personality Inventory) di Lembaga Psikologi MetaPROGRESS - Aulia Akbar Setyogomo; Denny Sagita Rusdianto; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MetaPROGRESS is a psychological consulting and human resource management institution located in Sidoarjo, Jawa Timur. One of the psychological tests it served is the MMPI (Minnesota Multiphasic Personality Inventory) which can assess personality traits and psychopathology. In practice, there are obstacles experienced in the process of interpreting the MMPI test results by them. Counselors sometimes make mistakes in writing reports on test results such as writing the client identity and matching the answer incorrectly. The process of interpreting the test results takes more than 15 minutes for 1 client and can be done longer if the test is done in groups. Also, they are constrained by receiving a number of files that must be taken. These problems may impact on other counselor's productive activities that can be delayed. The suggested solution is to build an interpretation system of MMPI test results with the waterfall software process model. The system is web-based so that it can be accessed by many computer platforms. The requirement engineering process produce 35 functional and 1 nonfunctional system requirement. 100% valid results are indicated by functional testing. In compatibility testing, there are no critical problems found on all browsers tested. Based on these results, this system can be a solution to their problem.